Manajemen Pendidikan dalam Implementasi Teknologi pada Perguruan Tinggi - Siti Sofiyah; Dina Satriani; Vina Vijaya Kusuma; Yeti Asmawati; Kristiani Tidarianti; Abdi Ramdan; Yanto Heryanto; Dian Evariana (Jurnal Pustaka Cendekia Pendidikan, 2026)
The accelerating integration of digital technologies into higher education has positioned educational management as a decisive factor that determines whether technological investment translates into genuine quality improvement. This study aims to synthesize current literature on the role of educational management in technology implementation across higher education institutions and to construct an integrative conceptual framework linking management, organizational readiness, implementation, and quality. A library research design was employed, drawing on twenty-two scholarly sources published mainly between 2021 and 2026 and retrieved from reputable databases including Scopus-indexed journals, Springer, ScienceDirect, Emerald, and MDPI, complemented by accredited national journals. Sources were screened for relevance and credibility and analyzed through thematic content analysis and comparative synthesis. The findings indicate that technology adoption (learning management systems, artificial intelligence, big data analytics, cloud computing, and smart campus) succeeds less because of the technology itself than because of managerial functions of planning, organizing, actuating, and controlling, mediated by organizational readiness, digital leadership, and institutional culture. The study contributes an integrative model in which educational management influences quality through organizational readiness and technology implementation. The principal limitation is its conceptual nature, requiring future empirical validation.